Effects of 8 Weeks of Resistance Training with Traband on Dynamic Balance in Young Soccer Players - mahmoud khodabakhshi; Sayyed Aliakbar Hashemi Javaheri; ahmad Ebrahimi Atri; majid Ebadi Fara (Biyumikānīk-i varzishī, 2016)
Objective: Keeping one's balance is a basic part of daily activities and it is an important factor in the performance of the athletic. The goal of this study was to study the effect of resistive exercises on young soccer players dynamic balance.